Bulletproof Ajax - Keith, Jeremy (Voices that matter., 2007)
Step-by-step guide reveals best practices for enhancing Web sites with Ajax A step-by-step guide to enhancing Web sites with Ajax. Uses progressive enhancement techniques to ensure graceful degradation (which makes sites usable in all browsers). Shows readers how to write their own Ajax scripts instead of relying on third-party libraries. Web site designers love the idea of Ajax--of creating Web pages in which information can be updated without refreshing the entire page. But for those who aren't hard-core programmers, enhancing pages using Ajax can be a challenge. Even more of a challenge is making sure those pages work for all users. In Bulletproof Ajax, author Jeremy Keith demonstrates how developers comfortable with CSS and (X)HTML can build Ajax functionality without frameworks, using the ideas of graceful degradation and progressive enhancement to ensure that the pages work for all users. Throughout this step-by-step guide, his emphasis is on best practices with an approach to building Ajax pages called Hijax, which improves flexibility and avoids worst-case scenarios.